Balance-sheet restructuring in Italy: an empirical analysis based on monetary circuit theory - Marcello Spanò (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2024)
Based on 25 years (1995-2019) of fully integrated sectoral data, this study builds on monetary circuit theory to examine the Italian experience of growing private debt followed by a long recession with balance-sheet restructuring. It is argued that this process cannot be identified as a typical balance-sheet recession. After the global financial crisis of 2007-2008, Italian firms increased financial sources from economic activities by retaining earnings, lowering wages, and disinvesting. Their deleverage, however, rested largely on the overall financial wealth reallocation that occurred after 2012, which was induced by monetary and fiscal policy, creating the conditions for households to increase net saving and to channel cumulated wealth from government securities and money balances towards equities.
Keywords: E12; E20; E63; 330; Sources of finance; Debt; Sectoral analysis; Money reflux; Economic policy